2017
DOI: 10.1088/1361-6560/aa7028
|View full text |Cite
|
Sign up to set email alerts
|

Online pretreatment verification of high-dose rate brachytherapy using an imaging panel

Abstract: Brachytherapy is employed to treat a wide variety of cancers. However, an accurate treatment verification method is currently not available. This study describes a pre-treatment verification system that uses an imaging panel (IP) to verify important aspects of the treatment plan. A detailed modelling of the IP was only possible with an extensive calibration performed using a robotic arm. Irradiations were performed with a high dose rate (HDR) Ir source within a water phantom. An empirical fit was applied to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 23 publications
3
48
0
Order By: Relevance
“…Source position verification using EPIDs also requires large and expensive systems that have limited availability. This study has shown that similar source position verification accuracy to EPIDs may be achieved with the MP system. Furthermore, the MP system has been shown to have a superior timing resolution of less than 1 ms .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Source position verification using EPIDs also requires large and expensive systems that have limited availability. This study has shown that similar source position verification accuracy to EPIDs may be achieved with the MP system. Furthermore, the MP system has been shown to have a superior timing resolution of less than 1 ms .…”
Section: Discussionmentioning
confidence: 57%
“…Real‐time source identification of dwell positions during HDR prostate brachytherapy treatments based on electronic portal imaging devices (EPIDs) have been performed previously . In one study, the authors retrospectively compared the planned vs measured source positions using an EPID embedded into the couch for eight treatment fractions, and the mean linear distance between the planned and measured dwell positions was found to be 1.8 mm (range 0.7–3.9 mm) .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous work explored the sourcetracking capacity of different detectors in HDR brachytherapy. [23][24][25][26][27][28] Some studies used an array of dosimeters placed on the patient's skin, and others a flat-panel detector. In a study of source-position tracking with a single-point detector in HDR brachytherapy, Johansen et al 24 used the dose values from the treatment planning system to develop a method to determine average source shifts within catheters.…”
Section: Introductionmentioning
confidence: 99%
“…This poor signal to noise ratio necessitates the use of longer integration times in the detector system and may therefore preclude the system from performing real-time source tracking analysis. This issue has been discussed in previous publications on the use of EPID devices for source tracking [13][14][15][16]. The Magic Plate system, however, is capable of operating with variable integration times between 14 -9900 μs, with a stable sampling frequency between 0.1 -10 kHz.…”
Section: Discussionmentioning
confidence: 99%
“…Source tracking of dwell positions during HDR pBT treatments based on electronic portal imaging devices (EPIDs) have been performed previously [13][14][15][16]. However, when used for HDR brachytherapy source tracking, these EPID based devices are required to operate using low frame rates due to poor signal to noise ratios, and when compounded with their inherently slow read out electronics, loss of data for short dwell times can occur [14].…”
Section: Iintroductionmentioning
confidence: 99%